Case Report: Recurring Peritonitis and Dialysis Failure in a Toddler on Peritoneal Dialysis - Mohammed, Enas H.; Chandy, Sajimol; Kadhi, Abderrahman E.; Shatat, Ibrahim F. (Frontiers in Pediatrics, 2021)
We report a case of a two-year-old-boy with end stage renal disease (ESRD) secondary to posterior urethral valves (PUV) on peritoneal dialysis (PD). Our patient developed multiple episodes of peritonitis, refractory anemia and feeding intolerance over a 12-month-period. He was treated with multiple courses of intraperitoneal antibiotics. Despite being on high-calorie formula, he was slowly thriving. The feeding intolerance was attributed to past history of prematurity, gastro-esophageal reflux disease and ESRD co-morbidities. He had anemia resistant to erythrocyte stimulating agents and iron supplementation. His family received re-training and mastered the PD techniques. They reported no breach of the aseptic techniques. His workup which included multiple AP abdominal XR-plain films were read as unremarkable and showed the gastrostomy tube (GT) and the PD catheter in good position. He completed his antibiotic courses as prescribed after each peritonitis episode, peritoneal fluid cultures repeated after each treatment completion showed no growth. During the last peritonitis episode, our patient developed ultrafiltration failure. A cross-table abdominal XR was obtained to evaluate the peritoneal catheter position and showed an intra-abdominal foreign body. During surgery, a needle was laparoscopically removed from the ileum and the PD catheter was replaced. Subsequently, our patient’s feeding intolerance and resistant anemia resolved. Finally PD was successfully resumed.